Desempenho de conjunto motor-gerador utilizando biocombustíveis sob cargas variadas - Rigotte, Marcio Roberto (2014)
The rising demand for energy, coupled with its high cost and the search for sustainability propitiated in recent years an increase in demand for renewable biofuels, including biodiesel. Although Brazil, and specifically Paraná, present agricultural vocation, with diversity of raw materials for biodiesel production, it remains tied to demand compulsory. This work aimed to evaluate the energetic performance of an engine-generator set using diesel oil and biodiesel of different feedstocks. The experiment was conducted in the Experimental Nucleus for Agricultural Engineering (NEEA), State University of West Paraná (UNIOESTE), located in Cascavel - Paraná, using entirely randomized design. The treatments were diesel oil, and three different types of biodiesel (crambe, soybean and waste frying oil) being used pure biodiesel (B100) and the binary blends B10, B20 and B50. The resistive loads used were 1, 2, 3, 4 and 5 kW for each type of fuel, a total of five replications. Among other observations, we evaluated the heating value, specific fuel consumption (CE) and energy efficiency (EE). The best CE was diesel with 0,349 Kg KW h-1 in the load 5 KW, followed by BC20-2 with 0,524 Kg kW h-1 and BC50-3 with 0,433 Kg kW h-1. Biodiesel has the CE nearest of the diesel with increasing resistive load, indicating that its use in operation closest the rated capacity is more efficient. Among the types of biodiesel, the crambe oil showed lower CE, with some values without significant differences (Tukey 5%) of the diesel CE, as BC20-4 with 0,383 Kg kW h-1 and BC10-5 with 0,367 Kg KW h-1. The best EE were DI-5 25,6%, BC100-5 25,5%, BC50-5 25,0%, BS100-5 24,8% and BORF100-5 24,6%. Pure biodiesel (B100) tends to show best EE that the binary blends used. The BC100 showed EE of 9,9 17,8, 21,8, 24,3 and 25,5% respectively for resistive load of 1, 2, 3, 4 and 50 KW. In the range of biodiesel evaluated, crambe oil obtained EE closer to diesel, and the BC100 exceeded diesel EE to the loads 2, 3 and 4